ALLERGY PREVENTION IN CHILDREN DURING THE INTRODUCTION OF COMPLEMENTARY FEEDING PRODUCTS - Т. V. Turti; S. G. Makarova; Ye. P. Zimina (Вопросы современной педиатрии)
The article covers modern approaches to the prevention of allergic diseases in children. We discuss the most common food allergens in the early childhood, main mechanisms of food tolerance formation and opportunities of dietary preventive measures in a risk group of the allergy development. One of the important issues, in practical terms, is the question of time and peculiarities of the complementary feeding introduction in this category of children. The own experience of use of hypoallergenic complementary feeding products in children from the risk group and with mild manifestations of atopy is presented.